Giving Prizes in Term Savings Products with Prizes (Siberkah) According to Sharia Economic Law at BMT Dana Ukhuwah Cicalengka Branch Bandung District - Nurazizah, Nury; Rosdiana, Rika; Wibawa, Ginan (Doktoral Ilmu Manajemen, Universitas Pasundan, 2023)
This research aims to determine the gift giving system in terms of savings products with prizes at BMT Dana Ukhuwah, Cicalengka Branch, Bandung Regency. As well as problems that occur in the implementation of prize giving which result in a mismatch between terms and conditions and those that occur in the field. In this research the outsider used empirical research by collecting data in the form of observations, interviews and documentation. Because with this method the author can interact directly with the data source so that the data the author finds will be very clear. The results of this research show that the term savings with prizes is one of BMT Dana Ukhuwah service programs. This prize will be given to customers who have fulfilled the terms and conditions. The existence of prizes in this term savings system makes customers interested in saving their funds in BMT Dana Ukhuwah. Gifts given to customers in the form of objects such as gas stoves, magicom, and gold according to the nominal amount of savings saved. Prizes will be given at the beginning of account opening with the deposit amount and the period determined at the time of agreement. In view of sharia economic law, giving gifts at the BMT Dana Ukhuwah branch Cicalengka Bandung Regency is permitted as long as it does not contain elements of gambling and no party is harmed.